ENGLISH LANGUAGE LEARNING STRATEGIES IN THE CONTEXT OF INCLUSIVE EDUCATION - Кадырбаева, Н.Ж.; Доценко, М.К. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2024)
The article is devoted to the problem of teaching students with special educational needs in English lessons. The relevance of this problem lies in the fact that it is necessary to ensure the general cultural, personal and cognitive development of children with SEN. The authors proposes some innovative technologies used when working with children with SEN in the process of inclusive education. These technologies will help teachers develop the skills and abilities of foreign language communication in children.
Keywords: inclusive education; innovative learning models; teaching children with SEN